Menelaah Hakikat, Instrumentasi, dan Praksis Demokrasi Pancasila Mahasiswa Akuntansi Universitas PGRI Adi Buana Surabaya - Rahmi Tara Iman Aisyah; Ratu Aimartasia; Achmad Ali Rizal; Vicha Cahyani Kueain; Ella Djamilah Syah; Icha Nurul Laili Fitrah; Muhammad Rizki Rizal Maulana; Aviv Syafiin Rifai’i; Muhammad Bintang Prayoga; Rayhan Kanza Albani; Gunita Gunita; Lizaristi Berliana Putri; Nazhwa Lahmirza Masyithoh; Suyono Suyono (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the nature, instrumentation and practice of Pancasila democracy for accounting students. Pancasila Democracy is a democratic system based on the values ​​of Pancasila, namely Belief in One Almighty God, Just and Civilized Humanity, Indonesian Unity, Democracy Led by the Wisdom of Wisdom in Deliberation/Representation, and Social Justice for All Indonesian People. Accounting students as agents of change have an important role in realizing Pancasila democracy. They need to understand the essence of Pancasila democracy, the instruments used to make it happen, and how to practice it in everyday life. This article aims to: 1). Analyzing the nature of Pancasila democracy 2). Identifying Pancasila democratic instruments 3). Studying the democratic practices of Pancasila for accounting students. The research method used is literature study by collecting opinions from various students. The research results show that Pancasila democracy is a unique democratic system and is in accordance with the cultural values ​​of the Indonesian nation. Pancasila's democratic instrumentation includes the constitution, laws and state institutions. Accounting students can practice Pancasila democracy in everyday life by: 1). Participate in political and social activities, 2). Maintaining tolerance and harmony between religious communities, 3). Preserving Indonesian culture, 4). Building a just and prosperous society. Knowledge and understanding of Pancasila democracy for accounting study program students is very important to create a democratic, just and prosperous Indonesia.